TIPE TALUS LICHEN PADA AREA GREENBELT PT. SEMEN INDONESIA (Persero) Tbk PABRIK TUBAN - Sriwulan Sriwulan; Dwi Oktafitria; Eko Purnomo (Prodi Biologi Universitas PGRI Ronggolawe, 2023)
Lichens are organism resulting from symbiosis of algae and fungi. These organisms are often used for monitoring of air quality as bio-indicators. This relates to its ability to respond to the presence of pollutants in the air. Sensitive lichens type, will not be found in locations with polluted air conditions. On the other hand, in locations with polluted environmental conditions, the type of lichen commonly found is tolerant lichen. The response of lichens to environmental conditions can be seen from the lichen body itself which is known as the thallus. This study aims to identify the types of lichen thallus found in the greenbelt area of ​​PT. Semen Indonesia (Persero) Tbk Tuban Factory. Sampling in this study was conducted at 4 locations, namely TLO, GRE, GTI, and VIE. The results showed that the lichens found in this study had thallus with crustose, fructicose, squamulose, and gelatinous types.